High absolute neutrophil count with type 2 diabetes is associated with adverse outcome in patients with coronary artery disease: A large-scale cohort study - He, Jining; Lin, Zhangyu; Song, Chenxi; Zhang, Rui; Wang, Haoyu; Yuan, Sheng; Bian, Xiaohui; Dong, Qiuting; Dou, Kefei (Frontiers in Endocrinology, 2023)
Background Inflammatory processes crucially modulate the development, progression, and outcomes of coronary artery disease (CAD). Since hyperglycemia could alter inflammatory responses, this study aimed to investigate the effect of ANC, a novel and rapidly available inflammatory biomarker, on the prognosis of patients undergoing PCI with or without type 2 diabetes (T2D). Methods A total of 7,826 patients with CAD hospitalized for PCI at Fuwai Hospital were consecutively recruited. According to the median ANC value, patients were stratified as having high ANC (ANC-H) or low ANC (ANC-L) and were further classified into four groups by T2D. The primary endpoint was major adverse cardiovascular and cerebrovascular events (MACCEs), including all-cause mortality, myocardial infarction, stroke, and target vessel revascularization. Results During a median follow-up of 2.4 years, 509 (6.5%) MACCEs were documented. Diabetic patients with increased ANC were at significantly higher risk of MACCEs (aHR, 1.55; 95% CI, 1.21–1.99; P = 0.001) compared to those in the ANC-L/non-T2D group (P for interaction between T2D and ANC categories = 0.044). Meanwhile, multivariable regression analysis demonstrated the highest MACCE risk in diabetic patients with a higher level of ANC than others (P for trend <0.001). Conclusion This study suggests that stratification of patients with elevated ANC and T2D could provide prognostic information for CAD patients undergoing PCI.